2018
DOI: 10.3390/ijgi7120485
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Dynamic Web-GIS Based Landslide Early Warning System for the Chittagong Metropolitan Area, Bangladesh

Abstract: This article aims to develop a Web-GIS based landslide early warning system (EWS) for the Chittagong Metropolitan Area (CMA), Bangladesh, where, in recent years, rainfall-induced landslides have caused great losses of lives and property. A method for combining static landslide susceptibility maps and rainfall thresholds is proposed by introducing a purposely-build hazard matrix. To begin with, eleven factor maps: soil permeability; surface geology; landcover; altitude; slope; aspect; distance to stream; fault … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…We found that out of seven studies only one study produced landslide inventory for the entire CHA [72]. Other studies focused on creating LSMs for the two largest urban parts of the CHA-Chittagong Metropolitan Area (CMA) [73,74] and Cox's Bazar municipality [75], as well as for landslide prone Rangamati district [76]. Landsat TM and OLI images Methodologically, many of these studies used remote sensing products as supporting tools to identify land degradation prone areas and calculate land loss or gain (e.g., [33,64,65].…”
Section: Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that out of seven studies only one study produced landslide inventory for the entire CHA [72]. Other studies focused on creating LSMs for the two largest urban parts of the CHA-Chittagong Metropolitan Area (CMA) [73,74] and Cox's Bazar municipality [75], as well as for landslide prone Rangamati district [76]. Landsat TM and OLI images Methodologically, many of these studies used remote sensing products as supporting tools to identify land degradation prone areas and calculate land loss or gain (e.g., [33,64,65].…”
Section: Erosionmentioning
confidence: 99%
“…We found that out of seven studies only one study produced landslide inventory for the entire CHA [72]. Other studies focused on creating LSMs for the two largest urban parts of the CHA-Chittagong Metropolitan Area (CMA) [73,74] and Cox's Bazar municipality [75], as well as for landslide prone Rangamati district [76]. Landsat TM and OLI images and MLC approach were used for mapping land use land cover change and developing indices (i.e., NDVI) [73,77], while Advanced Spaceborn Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM) (30 m) and ALOS-PALSAR DEM (12.5 m) were used for preparing topographic causal factors such as slope, aspect, profile and plan curvature using the GIS platform [76,78].…”
Section: Landslidesmentioning
confidence: 99%
“…Landslides are known to cause distress worldwide and are considered the third most significant natural hazard [1][2][3]. They are a form of mass wasting that includes a wide range of ground movements, such as rock falls, deep failure of slopes and shallow debris flows [4].…”
Section: Introductionmentioning
confidence: 99%
“…South Korea forecasts landslides and debris flows by analyzing rainfall and basin characteristics and using models to calculate the triggering factors. With the current advancement in radar technologies, studies are continuously conducted for predictions using radar data [10][11][12][13][14][15][16][17][18][19]. Therefore, the study attempted to establish a method that considers rainfall intensity and accumulated rainfall not as an independent factor but a function.…”
Section: Introductionmentioning
confidence: 99%